Factors contributing to the decline of votes in South Africa : a case study of Mankweng community - Seanego, M. J.; Mogoboya, M. J. (International Conference on Public Administration and Development Alternative (IPADA), 2019)
: One of the basic democratic rights of citizens of any country in the world is voting. However, global statistics depict a steady decline in voting from eligible voting population of the world, particularly the youth and to a lesser extent, the elderly. According to Statistics South Africa, in 2019, there were 26.1 million registered voters on the voters roll. However, 9 million South Africans who were eligible to vote did not register to do so. This decline indicates that eligible South African electorate's appetite to exercise their voting right has dissipated. The question is why? This article seeks to examine factors which contribute to the decline of votes in South Africa using Mankweng community as a case study. Its objective is to investigate reasons behind the low voter turnout among eligible South African voters, utilising Mankweng community as a microcosm. The researchers have used qualitative research method which adopted random sampling when accumulating data from Mankweng community members. Fifteen (15) eligible voters from a total population of twenty-eight (28) from Mankweng community were incorporated in the study for data collection. Open-ended interviews were used as data collection tools. Rational Choice Theory was employed to undergird the study. The study found that the majority of Mankweng community members of voting age, especially the youth and, to a lesser extent, the elderly believe that the government does not adequately add value to their lives. As a result of this vexing concern, South Africa is challenged by a worrying trend of dwindling voter turnout from its electorate. Keywords: Citizenship, Democracy, Elections, Electorate, Mankweng community, Rights, Voting
The 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Citizenship; Democracy; Elections; Electorate; Mankweng community; Rights; Voting; Democracy -- South Africa - Congresses; Ballot